Еколого-біологічна оцінка вічнозелених листяних чагарників, які використовуються в озелененні м. Запоріжжя - Pristupa, I.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
The indexes of growth, generative development, winter-resisting and droughtresisting of 19 evergreen leafy bushes species growing in the conditions of Zaporizhia are studied. The numbers of acclimatizati on are found on the base of data obtained. Estimation of perspective of further use of these species for planting of greenery in the Zaporizhia region is presented.